Detection of sea-surface wind patterns associated with convective systems and their evolution using a combination of Sentinel-1 and Radarsat-2 imagery. Issue 5 (3rd May 2020) - La, Tran Vu; Messager, Christophe
ABSTRACT: Synthetic Aperture Radar (SAR) can detect wind patterns induced by the Convective Systems (CS) downdraughts hitting the sea surface due to their high spatial resolution and large swath. Additionally, the combination of two successive SAR images (Sentinel-1 and Radarsat-2) with appropriate observation time delays may enable the observation of wind pattern evolution. The corresponding METEOSAT-10/11 infrared images to the SAR ones are used for the detection of deep convective clouds that are potentially associated with wind patterns. The current paper investigates two cases of time delays (1-minute and 5-minute) between two satellites. The estimated wind speeds by CMOD5.N on Sentinel-1 and Radarsat-2 images are almost the same for the background wind areas. However, the intensity of wind patterns on Radarsat-2 images (acquired 1 and 5 minutes later) is decreased, possibly due to a change of downdraught intensity according to observation time. In the 1-minute delay case, the drop of wind intensity is mainly observed for the intense spots (20–25 m s −1 ), while in the 5-minute delay case, it is noticed for both intense and moderate (10–15 m s −1 ) convection spots. The intensity of the high-wind convection spots decreases more quickly since the associated convective-scale downdraughts reach the sea surface more rapidly.